Strategies for Improving Teacher Performance Using a Local Expertise Approach: A Study Using POP-SDM - Rahmawati Rahmawati; Bibin Rubini; Lina Novita (Al-Qalam Institute, 2025)
This study explores strategies to enhance teacher performance using a local-expertise variable approach, with a focus on the local tradition of gotong royong (cooperation). Previous research has overlooked the impact of local customs on teacher performance. The research applies Human Resource Strengthening Modeling and Optimization (POP-SDM) and a multi-stage random sampling technique, involving 124 teachers from 9 private vocational schools in Bekasi Regency. Data analysis employs SEM-PLS 3 for path analysis, testing 7 direct and 3 indirect influences. The study integrates local expertise to improve teacher productivity by accounting for local customs. SITOREM analysis identifies the following prioritized areas for improvement: Salary/Income, Working Conditions, Promotion Opportunities, and Supervision, among others. The results show that 4 direct-effect hypotheses were accepted and 3 rejected, while 2 indirect effects were accepted and 1 rejected. The findings suggest that enhancing teacher performance requires focusing on job satisfaction, knowledge management, communication, and cooperation. By addressing the order of indicators identified through SITOREM, optimal solutions for improving teacher performance can be developed. This research emphasizes the importance of integrating local traditions into modern educational practices.